2021
DOI: 10.18553/jmcp.2021.21011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of lemborexant and other insomnia treatments: a network meta-analysis

Abstract: BACKGROUND: Insomnia is a common disorder associated with a substantial burden of illness, particularly in older adults. OBJECTIVE:To compare the efficacy and safety of lemborexant with specified other insomnia treatments through a systematic literature review and network meta-analysis (NMA). METHODS:Medline and Embase were systematically searched from inception to February 2019 and updated with a targeted search of PubMed for pivotal trials in March 2021. Randomized controlled trials in adults with primary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Secondly, no studies have directly compared suvorexant with lemborexant; the sSOL response rate used to measure efficacy was conservatively assumed to be the same for both drugs. The results of an NMA showed a statistically significant improvement in sSOL assessments after three months of treatment with lemborexant compared with that of suvorexant (McElroy et al, 2021 ). In addition, Kishi et al ( 2020 ) recently reported that both 5 and 10 mg lemborexant outperformed suvorexant (20/15 mg) and zolpidem ER (6.25 mg) in terms of the subjective time to sleep onset after one week.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Secondly, no studies have directly compared suvorexant with lemborexant; the sSOL response rate used to measure efficacy was conservatively assumed to be the same for both drugs. The results of an NMA showed a statistically significant improvement in sSOL assessments after three months of treatment with lemborexant compared with that of suvorexant (McElroy et al, 2021 ). In addition, Kishi et al ( 2020 ) recently reported that both 5 and 10 mg lemborexant outperformed suvorexant (20/15 mg) and zolpidem ER (6.25 mg) in terms of the subjective time to sleep onset after one week.…”
Section: Discussionmentioning
confidence: 99%
“…The response rates for suvorexant and zolpidem IR were based on a network meta-analysis (NMA) aimed at providing estimates of comparative efficacy and acceptability for up to 16 pharmacological treatments, including lemborexant, for insomnia disorder in adults (McElroy et al, 2021 ). The response rate for zolpidem IR was assumed to be the same as that for zolpidem ER, as the mean decrease in sSOL from baseline at four weeks did not significantly differ [−8.3 min; 95% credible interval (Crl), −17.5 to 0.4] between zolpidem IR and zolpidem ER (McElroy et al, 2021 ), and a direct comparison of responder rates for zolpidem ER in SUNRISE 1 was available. The response rate for suvorexant was conservatively assumed to be the same as that for lemborexant, as the data describing responder rates were unavailable due to the fact that no direct comparison was performed in SUNRISE 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The safety profile, severe adverse events and rates of withdrawals due to adverse events were similar for lemborexant and all the other treatments. 4 …”
mentioning
confidence: 99%